Distance education challenges: insight from a nationwide teacher-centric study post- COVID-19 for informed advancements - Alshaboul, Yousef; Alazaizeh, Manar; Abu-Tineh, Abdullah; Ghamrawi, Norma; Shal, Tarek (Frontiers in Education, 2024)
Scholars persistently explore the enormous effects of the COVID-19 epidemic on schooling, striving to comprehend its intricacies and derive significant perspectives for forthcoming endeavors. The research-based conclusions and suggestions are deemed potentially effective in closing the gap between theory and practice in literature. This is one of the few studies that connects problems with remedies as proposed by teachers. This national teacher-centric study uses a mixed-method methodology with a random sample of teachers from public and private schools in the State of Qatar to look extensively into the problems faced during the pandemic. In the sample, there were 45 instructors who participated in semi-structured online interviews and 1553 teachers who answered an online questionnaire. The study points out a number of issues, such as teachers' deficiency in pedagogical competencies, sophisticated technological proficiency in the classroom, curriculum density, inadequate teaching strategies, challenges with determining students' needs and obtaining an honest and realistic assessment that accurately represents the students' level of learning, and the lack of extracurricular activities. According to the findings, the challenges were influenced by a number of factors, including year of experience, gender, age, specialization, education level, and extracurricular activities. We need to leverage the lessons learned to shape the future course that distance education takes to move forward, guided by our observations and insights.1 Commented [YA1]: Comment # 1 (Reviewer 2): The abstract covered the main points needed. However, it would be good if the authors could highlight what has been reported in the past and the research gap that justifies this article.